Nanomaterials in Food - Current and Future Applications and Regulatory Aspects. (May 2015) - Aschberger, K; Gottardo, S; Amenta, V; Arena, M; Moniz, F Botelho; Bouwmeester, H; Brandhoff, P; Mech, A; Pesudo, L Quiros; Rauscher, H; Schoonjans, R; Vettori, M Vittoria; et al.
Abstract: Nanotechnology can contribute to the development of innovative applications in the agriculture, food and feed sector by e.g. enabling improved delivery of nutrients or increased efficacy of agrichemicals. It is expected that applications will increase in the near future and may therefore become a relevant source of human exposure to nanomaterials (NM). To gain more up-to date information, RIKILT and the Joint Research Centre (JRC) were commissioned by the European Food Safety Authority (EFSA) to prepare an inventory of currently used and reasonably foreseen applications of NM in agriculture and food/feed production and carried out a review of regulatory aspects concerning NM in both EU and non-EU countries. An analysis of the information records in the inventory shows that nano-encapsulates, silver and titanium dioxide are the most frequent type of NM listed and that food additives and food contact materials are the most frequent types of application. A comparison between marketed applications and those in development indicates a trend from inorganic materials (e.g. silver) towards organic materials (nano-encapsulates, nanocomposites). Applications in novel food, feed additives, biocides and pesticides are currently mostly at a developmental stage. The review of EU and non-EU legislation shows that currently a few EU legal acts incorporate a definition of a nanomaterial and specific provisions for NM, whereas in many non-EU countries a broader approach is applied, which mainly builds on guidance for industry.